Synthesis and Spectroscopic, Studies of Some New Piperidin-4-one Derivatives - ALkhafaji, Dalia Saad Mahdi Said; Fenjan, Abdel-Amir Mutlak; Mohammad, Abdul-Karim Talaq (Al-Nahrain Journal of Science, 2018)
The homologous series of 2,6-bis(4-Subtituetphenyl)-3-methylpiperidin-4-one compounds were synthesized using Mannich condensation. Then Five series have been synthesized by reaction of different reagents of semicarbazide. With 2,6-bis(4-Subtituetphenyl)-3-methylpiperidin-4-one to sythesize target compounds 2a-2f, 2a-2f, 3a-3f, 4a-4f, 5a-5f and 6a-6f. The chemical structures of the molecules were characterised by FT-IR, 1D NMR and CHN elements analysis.